Literasi Penerapan Pajak Penghasilan Badan Dan Perlakuan Akuntansi - Agustina, Siti Sarah; Sugiyanto, Sugiyanto; Sumaryana, Fitriana Dewi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
One type of tax that contributes to tax revenues is income tax. KUD Sinar Jaya Producer Cooperative is one of the corporate taxpayers that is obliged to pay corporate income tax. However, in reality, the KUD Sinarjaya Producer Cooperative has not yet fulfilled its obligations to pay, deposit, and report corporate income tax. This is because there is still a lack of knowledge from the cooperative. The research method employed is a qualitative approach with descriptive analysis. Based on the results of the study, it is known that the literacy level of cooperative taxation, especially the corporate income tax of the KUD Sinarjaya Producer Cooperative, is included in the low category. The Sinarjaya KUD Producer Cooperative can calculate corporate income tax according to Government Regulation Number 23 of 2018 at a rate of 0.5%. The KUD Sinarjaya Producer Cooperative must deposit corporate income tax every month before the 15th of the following month. KUD Sinarjaya Producers Cooperative must report corporate income tax every month before the 20th of the following month.